The 'war on terror' and the new periphery - Ryan, Maria (University Press of Kentucky, 2017)
This chapter exmaines the emergence of 'peripheral' fronts in the Bush administration's 'war on terror.' Since this 'war' was conceived from its inception as global in scope, it permitted the development of both 'core' and 'peripheral' fronts - the latter emerging in the Philippines, Georgia, and across Sub-Saharan Africa. In each of these areas, the Bush administration identified a confluence of material interests - such as energy security - and a possible threat from Islamist terrorism, and launched a series of Foreign Internal Defense campaigns, in parternership with local governments, to prevent the emergence of terrorism there and safeguard other US interests on the new 'periphery.'